Is unconditional basic income a viable alternative to other social welfare measures? - Ugo Colombino (IZA World of Labor, 2019)
Globalization and automation have brought about a tremendous increase in productivity, with enormous benefits, but also a dramatic reallocation of jobs, skills, and incomes, which might jeopardize the full realization of those benefits. Current social policies may not be adequate to successfully redistribute the gains from automation and globalization or to advance the reallocation of jobs and skills. Under certain circumstances, an unconditional basic income might be a better alternative for achieving these goals. It is simple, transparent, and has low administrative costs, though it may require higher taxes or a cut/reallocation of other public expenditures.
Keywords: I38; H24; 330; basic income; means testing; incentives; redistribution; globalization; automation